Pengaruh Kompetensi dan Pelatihan terhadap Kinerja Karyawan PT. Adaro Energy Tbk - Ilman Ataunur; Eny Ariyanto (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstarctTo support the strategic objectives and facing the challenges of a constantly evolving organization, it needs employees with high performance. If the performance of employees increased the effectiveness and productivity of the company will increase as well. Competence and training are factors that lead to employee performance improvement. Competency can help organizations create a culture of high performance. While, the training that has been developed through phases planned and programmed process will have a direct impact on employee performance. This study aims to analyze how strong the influence of competence and training to employees performance of PT Adaro Energy Tbk, either partially or simultaneously. The research method used was survey with the design of associative research. Research hypothesis had been tested using multiple linear regression. From the research results proved the competence contributed significantly strong positive effect on performance. However, training gave weakly significant positive effect on performance. Simultaneously, competence and training had a dominant significant positive effect on employee performance, which is showed by a coefficient of determination of 73.6%.